Evolution of the China Railway Express in the context of policy support, trade trends, and infrastructure supply - Manuel Benard; Runze Yu; Wenjing Pu (Asian Development Bank Institute (ADBI), 2024)
This paper delves into the developmental trajectory and future prospects of China Railway (CR) Express, a containerized railway freight service between the People's Republic of China (the PRC) and Europe, and examines the associated infrastructure investment needs for enhancing Eurasian freight transport. Since its establishment in 2011, CR Express has demonstrated remarkable growth, resilient even in the face of challenges such as the COVID-19 pandemic and the onset of the Russian invasion of Ukraine. The substantial expansion of CR Express over the past decade can be partially attributed to generous subsidies and favorable policies. While it is anticipated that government subsidies will gradually be phased out, the ongoing role of favorable policies will remain pivotal in shaping the trajectory of CR Express's future growth. Despite the dynamic evolution of the global trade landscape, the robust and steadily growing trade relationship between the PRC and Europe provides a solid foundation for CR Express to sustain its growth momentum. CR Express is also poised to capitalize on the growing demand for high-value products, including electronics, auto parts, high-end apparel, machinery, and premium furniture, as well as time-sensitive goods such as fresh produce, everyday clothing, and seasonal toys. However, the growth potential of CR Express faces impediments in the form of infrastructure limitations and operational challenges. Bottlenecks at ports, railways, and logistics hubs, coupled with issues like insufficient standardization, technical constraints, and service-related challenges, exert a negative impact on the overall efficiency and attractiveness of CR Express. In response to these constraints, concerted efforts are underway encompassing infrastructure construction and modernization initiatives, as well as the digitalization of logistics services. Investment opportunities emerge in the form of infrastructure construction and upgrades, along with the adoption of proven new technologies and digital solutions to enhance the efficiency and competitiveness of railway services.
Keywords: L92; F1; P45; R41; O24; 330; China Railway Express; PRC-Europe trade; Eurasian freight transport; ports; railways; logistics